2018
DOI: 10.1002/ps.4792
|View full text |Cite
|
Sign up to set email alerts
|

Ambrosia artemisiifolia as a potential resource for management of golden apple snails, Pomacea canaliculata (Lamarck)

Abstract: The results indicate that chemical compounds produced by A. artemisiifolia may be useful for population management of GAS in rice fields. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…Thus, the toxicity index at the same values illustrated that chloroform and hexane extracts of nutsedge were 75.0 and 57.4 % as effective as nightshade by chloroform and primpernel by hexane. Toxic action of plant extracts as molluscicides on land snails was also reported by Ghamry (1997) using Anagallis arvensis extract; by Ebenso (2004) using Azadirachta indica extract; by Abd El-Halim (2007) using Foeniculum vulgare l. extract; by Shabad (2010) using Artemisia annua extract; by Anjali et al (2014) using Solanum nigrum extract and by Ding et al (2018) using Ambrosia artemisiifolia extract.  Weed extracts as antifeedants:…”
Section:  Weed Extracts As Contact Poisonsmentioning
confidence: 62%
See 1 more Smart Citation
“…Thus, the toxicity index at the same values illustrated that chloroform and hexane extracts of nutsedge were 75.0 and 57.4 % as effective as nightshade by chloroform and primpernel by hexane. Toxic action of plant extracts as molluscicides on land snails was also reported by Ghamry (1997) using Anagallis arvensis extract; by Ebenso (2004) using Azadirachta indica extract; by Abd El-Halim (2007) using Foeniculum vulgare l. extract; by Shabad (2010) using Artemisia annua extract; by Anjali et al (2014) using Solanum nigrum extract and by Ding et al (2018) using Ambrosia artemisiifolia extract.  Weed extracts as antifeedants:…”
Section:  Weed Extracts As Contact Poisonsmentioning
confidence: 62%
“…Synthetic pesticides lead to environmental pollution and pest resistance with their effects on the beneficial living organisms and phytotoxicity. The toxic effect of plant extracts against the land snail Monacha obstructa was reported by other researchers (Speiser et al 1992;Ghamry 1997;Dodds and Hendrson 2002;Ebenso 2004;Shabad 2010;Anjali et al 2014;Ghaly 2016 andDing et al 2018). The objective of the present investigation is to study the molluscicidal effect of three weed extracts namely primpernel , nightshade and nutsedge against the adult stage of land snail M. obstructa as well as identification of chemical components of the more active extract using GC/MS analysis.…”
Section: Introductionmentioning
confidence: 68%
“…The cardiac glycosides fraction from Nerium indicum leaves had a 48‐h LC 50 of 20.12 μg/mL [124] . The methanol extract of Ambrosia artemisiifolia showed a 24‐h LC 50 of 194 μg/mL, with the sesquiterpene lactones psilostachyin (LC 50 =15.9 μg/mL) and psilostachyhin B (LC 50 =27.0 μg/mL) as the active constituents [125] . The methanol extract of leaves and twigs of Aglaia duperreana showed molluscicidal activity against P. canaliculata with a 72‐h LC 50 of 33.4 μg/mL [126] .…”
Section: Resultsmentioning
confidence: 99%
“…Molluscicidal activity of essential oils and pure compounds were evaluated according to the protocol of Ding and co‐workers [125] with slight modifications. For each assay, 150 mL of water containing 20 snails were placed into 250‐mL beakers and aliquots of the essential oils dissolved in EtOH (1 % stock solution) were then added.…”
Section: Methodsmentioning
confidence: 99%
“…Previous phytochemical studies on this plant reported several sesquiterpene lactones, triterpenes, polyamines, flavonoids and their derivatives, some of which are reported to have beneficial effects, such as molluscicidal, insecticidal, anti-inflammatory, antithrombin, and neuroprotective activities. [3][4][5] In recent years, the secondary metabolites in pollen and their potential role have received much attention. [6,7] As part of ongoing phytochemical research, we studied the inflorescence of A. artemisiifolia distributed in the Guangxi province of China.…”
Section: Introductionmentioning
confidence: 99%